Can dairy value chain projects change gender norms in rural Bangladesh? Impacts on assets, gender norms, and time use. - Siddiquee, N.A.; Tanvin, K. (International Food Policy Research Institute, 2014)
The goal of CARE - Bangladesh’s Strengthening the Dairy Value Chain Project (SDVCP) is to improve the dairy-related incomes of 35,000 households in Northwest Bangladesh. To achieve its goal, SDVCP addresses the major challenges to improving smallholder participation in the value chain, namely farmer mobilization and education, access to markets for their milk, and access to productivity - enhancing inputs. The project assists in the formation of dairy farmer groups as well as increasing women’s participation in the dairy value chain, particularly in such nontraditional occupations as milk collectors and livestock health workers. The SDVCP evaluation looks at how both tangible and intangible assets may have changed, particularly for women, as an outcome of the intervention.